Volumetric and cephalometric evaluation of the upper airway of class III patients submitted to maxillary advancement - Santiago, Thais Mazeu; Moura, Lucas Borin; Gabrielli, Marisa Aparecida Cabrini; Spin-neto, Rubens; Pereira-filho, Valfrido Antonio (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
AbstractIntroduction Anteroposterior maxillary deficiency can be associated with a decrease of upper airway volume. Maxillary advancement can improve the upper airway space.Aim To correlate cephalometric (2D) and volumetric (3D) measurements of the upper airway in class III patients treated by maxillary advancement.Material and method This retrospective transversal study was performed in ten adult patients submitted to maxillary advancement for correction of class III deformity secondary to maxillary anteroposterior deficiency. The Cone beam tomography files included in the medical records were used: (T1) pre-operative and (T2) 6 to 8 months postoperative. The DICOM files were imported and reconstructed for volumetric and cephalometric evaluation of the upper airway, as divided into nasopharynx, oropharynx and hypopharynx (Arnett & Gunson FAB Surgery).Result Age ranged from 26 to 55 years with a mean of 36.3±9.2 years. There were no statistically significant differences for cephalometric and volumetric parameters of the three pharyngeal regions between T1 and T2 periods. This was due to the small amount of maxillary advancement necessary to correct the maxillary deformity in the studied patients (4.7±1.89mm). The correlation between area and volume was not statistically significant only for preoperative measurements of the nasopharynx (r=0.30, p=0.40). It was significant for the other regions and evaluation periods (p<0.05).Conclusion Small maxillary advancements do not result in significant increases in airway dimensions.

ResumoIntrodução A deficiência anteroposterior da maxila pode estar associada com a diminuição do volume da via aérea superior. O avanço de maxila por resultar em um aumento do espaço aéreo superior.Objetivo Correlacionar mensurações cefalométricas (2D) e volumétricas (3D) da via aérea superior em pacientes classe III tratados por meio de avanço maxilar.Material e método Este estudo retrospectivo transversal foi realizado em dez pacientes adultos submetidos ao avanço de maxila para correção de deficiência anteroposterior de maxila e deformidade classe III. Foram incluídos os dados de tomografias computadorizadas Cone beam em dois períodos: pré-operatório (T1) e pós-operatório de 6 a 8 meses (T2). Os arquivos DICOM foram importados e reconstruídos para avaliação volumétrica e cefalométrica da via aérea superior, dividida em nasofaringe, orofaringe e hipofaringe (Arnett & Gunson FAB Surgery).Resultado A idade variou de 26 a 55 anos, com média de 36,3±9,2 anos. Não foram verificadas diferenças estatisticamente significantes para os parâmetros cefalométricos e volumétricos das três regiões da faringe entre os períodos T1 e T2. Este resultado ocorreu devido à pequena quantidade de avanço maxilar (4,7±1,89mm) necessário para a correção da deformidade na amostra. A correlação entre área e volume não foi estatisticamente significante apenas para as mensurações pré-operatórias da nasofaringe (r=0,30; p=0,40). Nas outras regiões e períodos a correlação foi estatisticamente significante (p<0,05).Conclusão Avanços maxilares de pequenas dimensões não resultam em um aumento significativo das dimensões da via aérea superior.
Avaliação volumétrica e cefalométrica da via aérea superior em pacientes classe III submetidos a avanço de maxila
Keywords: Orthognathic surgery; airway remodeling; retrognathia; Cirurgia ortognática; remodelação das vias aéreas; maxila